2017
DOI: 10.1080/00380768.2017.1401907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidizing and reducing agents in soil on methane production in Southeast Asian paddies

Abstract: Methane is one of the greenhouse gases emitted from paddy soil ecosystems and may induce global warming and climate change; therefore, mitigation options are urgently required to establish mitigation technology to reduce methane emission without affecting rice production. Methane is produced by a balance between oxidizing agents (such as iron) and reducing agents (easily decomposable soil organic matter), according to the so-called Takai theory. To evaluate options for mitigating methane production potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In these studies, it was also found that CH 4 production decreased when Fe and fertilizers containing S were added (Inubushi, Umebayashi, and Wada 1990a;Inubushi et al 1997b;Furukawa, Tsuji, and Inubushi 2001). The balance and relationship between oxidizing agents, especially soil Fe, and reducing agents, namely soil organic matter, on methane production was investigated in Southeast Asian paddy, and results showed a similar relationship between oxidizing and reducing agents as has been observed in Japanese paddy soils (Inubushi et al 2018).…”
Section: Organic Matter Decomposition and Methane Production In Paddy Soilmentioning
confidence: 61%
“…In these studies, it was also found that CH 4 production decreased when Fe and fertilizers containing S were added (Inubushi, Umebayashi, and Wada 1990a;Inubushi et al 1997b;Furukawa, Tsuji, and Inubushi 2001). The balance and relationship between oxidizing agents, especially soil Fe, and reducing agents, namely soil organic matter, on methane production was investigated in Southeast Asian paddy, and results showed a similar relationship between oxidizing and reducing agents as has been observed in Japanese paddy soils (Inubushi et al 2018).…”
Section: Organic Matter Decomposition and Methane Production In Paddy Soilmentioning
confidence: 61%
“…Moreover, as turbidity levels in both reservoirs were low, it is unlikely that sediments affected the measurements made by the probe. Further investigation is necessary to identify what factors are contributing to making the reservoirs reducing environments as high concentrations of electron donors such as easily decomposable soil organic matter can also be the cause of the detected low ORP levels (INUBUSHI, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Low O 2 availability could slow microbial respiration and activity (Hall and Silver, 2015;McGroddy and Silver, 2000). When O 2 is depleted in soil, Fe undergoes the oxidation and reduction of biogeochemical reactions (Inubushi et al, 2018). Therefore, O 2 accessibility has significant impacts on both redox and SOM mineralization.…”
Section: The Influence Of O 2 On Som Mineralizationmentioning
confidence: 99%